Targeting the hallmarks of aging: mechanisms and therapeutic opportunities - Sanada, Fumihiro; Hayashi, Shinichiro; Morishita, Ryuichi (Frontiers in Cardiovascular Medicine, 2025)
Aging is a complex biological process characterized by a gradual decline in cellular and physiological function, increasing vulnerability to chronic diseases and mortality. It involves a set of interconnected mechanisms known as the hallmarks of aging, including genomic instability, telomere attrition, epigenetic alterations, loss of proteostasis, mitochondrial dysfunction, cellular senescence, stem cell exhaustion, altered intercellular communication, and dysregulated nutrient sensing. These processes act at molecular, cellular, and systemic levels, contributing to age-related disorders such as neurodegeneration, cardiovascular disease, and metabolic syndromes. Emerging therapeutic strategies aim to delay or reverse aging by targeting specific hallmarks. These include senolytics to eliminate senescent cells, NAD+ boosters and mitophagy inducers to improve mitochondrial health, epigenetic reprogramming, and caloric restriction mimetics such as metformin and rapamycin to modulate nutrient-sensing pathways. Advances in regenerative medicine, gene editing, and organ cross-talk modulation are also contributing to the development of personalized, multi-targeted anti-aging therapies. Integration of omics technologies and biomarker research is expected to enhance our ability to monitor biological aging and optimize interventions for healthy longevity. This review highlights the current understanding of the hallmarks of aging and explores potential treatment strategies in light of our recent findings.